Severe chronic kidney disease is associated with poor survival after initial CRT‐defibrillator tachyarrhythmia therapy. Issue 1 (5th December 2019) - Adelstein, Evan C.; Saba, Samir; Jain, Sandeep; Wang, Norman C.
Abstract: Background: Implantable cardioverter‐defibrillator (ICD) recipients who receive appropriate device therapies have limited survival, and survival benefit in chronic kidney disease (CKD) has been questioned. We examined the association between CKD and survival after cardiac resynchronization therapy (CRT)‐defibrillator tachyarrhythmia therapies. Methods: We compared overall survival after appropriate shocks or anti‐tachycardia pacing in 439 CRT‐defibrillator recipients with left ventricular ejection fraction (LVEF) ≤35%, non‐right bundle‐branch block QRS pattern, and QRS duration >130 ms according to glomerular filtration rate (GFR) at implant, including 31 patients with GFR ≤30, 164 patients with GFR 31‐60, and 244 patients with GFR >60. At least one shock occurred in 302 patients (24 with GFR ≤30, 102 with GFR 31‐60, and 176 with GFR >60). Serial echocardiograms were also compared. Results: Patients were followed 64 months (interquartile range [IQR]: 29‐94) after implant, including 32 months (IQR: 12‐61) after first therapy. Time to first therapy or shock was similar across GFR groups. However, survival after first therapy declined directly with declining GFR ( P  < .001), with median postshock survival of 90 days for GFR ≤30 (95% confidence of interval [CI]: 0‐233), 612 days (95% CI: 365‐859) for GFR 31‐60, and 1672 days (95% CI: 1396‐1948) for GFR >60. Declining GFR category, ischemic heart disease, diabetes, and increasing age were independently associated with increased postshock mortality. Echocardiographic response was similar across GFR groups and was not associated with post‐therapy survival. Conclusions: Survival after appropriate tachyarrhythmia therapies, particularly shocks, is attenuated in patients with GFR ≤30. This raises concern over potential lack of survival benefit conferred by CRT‐defibrillators versus CRT‐pacemakers in this population.